(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
This article presents the topogeodetic survey results of geodetic network points around the quarry "Zarbant". The plan and elevation points of the triangulation network are selected on a 1:100000 scale map. For GNSS (in English “Global Navigation Satellite System”, GNSS) measurements, the search and reconnaissance of SGN (state geodetic network) points and reference mine survey plug described on the topographic map was performed. The enterprise of the Republic of Uzbekistan "SAMGEODEZIST" reconnaissance of geodetic signals and centers installed in accordance with the requirements for new GPS points installation. A scheme of a combined geodetic network was developed in which measurements were to be made using angle measurements and navigation instruments. The right-angled coordinates of these points are obtained in the conventional coordinate system with subsequent abbreviations to the global geodetic network, and the elevations were calculated in the Baltic Altitude System (BAS-77).